(untitled) (Journal of Basic and Applied Research in Biomedicine, 2024)
A cross-sectional study involving microbiological analysis was conducted from March 2021 to August 2021 in Jigjiga town to isolating and identifying Salmonella and E. coli from raw meats of camels and bovines slaughtered at the Jigjiga municipal abattoir and assessing possible associated related risk factors for the isolates. A total of 384 examined samples for the presence of Salmonella and E. coli. From the total samples examined, 64 (16.7%) and 44 (11.5%. were found to be E. coli and Salmonella positive respectively. Out of the 199 meat samples taken from camel, 31 (15.6%) and 32 (16.1%) were found positive for Salmonella and E. coli respectively while a total 185 meat samples of bovines, 13 (7%) and 32 (17%) were found positive for Salmonella and E. coli, respectively. In the univariable logistic regression analysis result, Salmonella revealed a statistically significant difference among different ages (OR (CI) = 2.36 (1.195–4.679); p-value = 0.013). The multivariable regression analysis showed there was no statistically significant difference between the two sex groups (OR (CI) = 2.01 (0.892–4.544); p = 0.092). In an univariable logistic regression analysis result, the odds of meat contamination in young-aged animals with E. coli were three times higher than in adult animals, showing a statistically significant difference (OR = 2.83 (1.567–5.095; p = 0.001). The prevalence of E. coli was higher in animals with poor body condition (31.9%), followed by medium (15.5%) and good body-conditioned animals (1.8%). In the multivariable logistic regression analysis, the odds of contamination of samples with E. coli from poor-body condition animals were 22 times higher than samples taken from good-body condition animals (OR (CI) = 21.8 (5.022 - 95.059); p = 0.000). To prevent cross-contamination of Salmonella and E. coli, hygiene must be improved, standardized procedures, and training programs should be implemented. Further studies on molecular characterization and serotyping of these species are also needed.